It Depends: Environmental Context and the Effects of Faultlines on Top Management Team Performance - Cooper, Danielle; Patel, Pankaj C.; Thatcher, Sherry M. B. (Organization Science, 2014)
Informational faultlines, the alignment of team member task-related attributes to form subgroups, are important in explaining team performance. Although informational faultlines may promote specialization and division of labor, they may also increase communication and coordination costs. Integrating work on the categorization-elaboration model, social identity theory, and contingency theory, we posit that facets of a team’s external environment moderate the effects of informational faultlines on performance. Using a sample of 380 top management teams, we examine moderation effects of environmental dynamism, complexity, and munificence. We find that informational faultline strength positively affects firm performance under low environmental dynamism, high complexity, and high munificence, but it negatively affects firm performance under high environmental dynamism, low complexity, and low munificence. We discuss the implications of our findings for theory and practice.